Analysis of Needs for Developing Higher Order Thinking Skills Test Instruments in Chemistry Learning Model Course - Jayanti, Etrie (Chemistry Education Department of Education and Teaching Faculty, 2024)
At the university level, developing higher-order thinking skills (HOTS) for college students is very important. Therefore, regular practice with higher-order thinking skills questions is necessary for college students. The absence of research identifying the use of higher-order thinking skills questions in one of the chemistry education programs, specifically in the course on the chemistry learning model, serves as the background for this study. This research aims to analyze the need to develop higher-order thinking skills test instruments in the learning model course. This study is part of the initial stage of research and development, specifically part of the define phase of the 4-D development model. The research involves lecturers and college students from the Chemistry Education Study Program at an Islamic University in South Sumatra. The data obtained from this research are qualitative data presented in descriptive form, including document analysis results and interview data from lecturers and college students. The instruments used to collect the research data include documentation and interview guidelines. Based on the data analysis results, it was found that the mid-semester and final-semester exam essay questions are not yet optimally adequate in facilitating college students to think at a higher level and in accommodating all the materials/topics in the chemistry learning model course. The essay questions that have been used so far tend to utilize operational verbs that fall into the category of low-order thinking skills. Therefore, developing higher-order thinking skills test instruments for the chemistry learning model course is necessary.